The role of the bronchial provocation challenge tests in the diagnosis of exercise-induced bronchoconstriction in elite swimmers. Issue 10 (23rd October 2008) - Castricum, A; Holzer, K; Brukner, P; Irving, L
Abstract : Background: The International Olympic Committee–Medical Commission (IOC-MC) accepts a number of bronchial provocation tests for the diagnosis of exercise-induced bronchoconstriction (EIB) in elite athletes, none of which have been studied in elite swimmers. With the suggestion of a different pathogenesis involved in the development of EIB in swimmers, there is a possibility that the recommended test for EIB in elite athletes, the eucapnic voluntary hyperpnoea (EVH) challenge, may be missing the diagnosis in elite swimmers. Objective: The aim of this study was to assess the effectiveness of the EVH challenge, the field swim challenge and the laboratory cycle challenge in the diagnosis of EIB in elite swimmers. Design: 33 elite swimmers were evaluated on separate days for the presence of EIB using 3 different bronchial provocation challenge tests: an 8 minute field swim challenge, a 6 minute laboratory EVH challenge, and an 8 minute laboratory cycle challenge. Main outcome measurements: Change in forced expiratory volume in 1 second (FEV1 ) pre and post test protocol. A fall in FEV1 from baseline of ≥10% post challenge was diagnostic of EIB. Results: Only 1 of the 33 subjects (3%) had a positive field swim challenge with a fall in FEV1 of 16% from baseline. 18 of the 33 subjects (55%) had a positive EVH challenge, with a mean fall in FEV1 of 20.4 (SD 11.7)% from baseline. 4 of the subjects (12%) had a positive laboratory cycle challenge, with a mean fall in FEV1 of 14.8 (4.7)% from baseline. Only 1 of the 33 subjects was positive to all 3 challenges. Conclusions: These results suggest that the EVH challenge is a highly sensitive challenge for identifying EIB in elite swimmers, in contrast to the laboratory and field-based exercise challenge tests, which significantly underdiagnose the condition. The EVH challenge, a well-established and standardised test for EIB in elite winter and summer land-based athletes, should thus be used for the diagnosis of EIB in elite swimmers, as recommended by the IOC-MC.